NOVEL TECHNIQUES FOR MITIGATION OF INTENSITY NOISE AND BEAT NOISE IN SAC OCDMA SYSTEMS - ALHASSAN ALI, AHMED MOHAMMED (2014)
Spectral amplitude coding optical code division multiple access (SAC OCDMA) is a low cost multi access scheme that is in consideration for deployment in future high speed optical networks. However, SAC OCDMA systems' performance is limited by intensity noise when incoherent sources are implemented or beat noise when coherent sources are implemented.